2014
DOI: 10.1021/jm500629e
|View full text |Cite
|
Sign up to set email alerts
|

Multistage Screening Reveals Chameleon Ligands of the Human Farnesyl Pyrophosphate Synthase: Implications to Drug Discovery for Neurodegenerative Diseases

Abstract: Human farnesyl pyrophosphate synthase (hFPPS) is the gate-keeper of mammalian isoprenoids and the key target of bisphosphonate drugs. Bisphosphonates suffer from poor "drug-like" properties and are mainly effective in treating skeletal diseases. Recent investigations have implicated hFPPS in various nonskeletal diseases, including Alzheimer's disease (AD). Analysis of single nucleotide polymorphisms in the hFPPS gene and mRNA levels in autopsy-confirmed AD subjects was undertaken, and a genetic link between hF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(107 citation statements)
references
References 52 publications
4
103
0
Order By: Relevance
“…The one-site-binding pattern observed here is a consequence of the enzyme closure, which renders the allosteric pocket inaccessible to the substrates. Analogous results demonstrating the biased binding (that is, binding exclusively to the allylic substrate site in the presence of Mg 2+ ) have been confirmed crystallographically with allosteric BPs912. In contrast to the binding of DMAPP and GPP, FPP binding was not affected by Mg 2+ (Table 2).…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…The one-site-binding pattern observed here is a consequence of the enzyme closure, which renders the allosteric pocket inaccessible to the substrates. Analogous results demonstrating the biased binding (that is, binding exclusively to the allylic substrate site in the presence of Mg 2+ ) have been confirmed crystallographically with allosteric BPs912. In contrast to the binding of DMAPP and GPP, FPP binding was not affected by Mg 2+ (Table 2).…”
Section: Resultssupporting
confidence: 59%
“…Interestingly, the binding mode of FPP differs from those of the allosteric BPs reported earlier910. Their pyrophosphate/BP groups interact with the enzyme differently from one another and do not overlap when superimposed (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Following these initial reports, in silico screening identified bisamidine-type inhibitors of hFPPS (e.g., 17 ) (Lindert et al, 2013), although the binding mode of these compounds has also not been reported. In our own efforts, multistage biochemical and structural screening led to the discovery of thienopyrimidine analogs (e.g., 18 ) that bind to the same allosteric pocket as compound 13 and exhibit equivalent in vitro potency (De Schutter et al, 2014). …”
Section: Isoprenoids Fpps/ggpps and Neurodegeneration—the Current Hypmentioning
confidence: 99%